Necrostatin‐1 supplementation enhances young porcine islet maturation and in vitro function. (18th September 2019) - Lau, Hien; Corrales, Nicole; Alexander, Michael; Mohammadi, Mohammad Rezaa; Li, Shiri; Smink, Alexandra M.; de Vos, Paul; Lakey, Jonathan R. T.
Abstract: Background: Necroptosis has been demonstrated to be a primary mechanism of islet cell death. This study evaluated whether the supplementation of necrostatin‐1 (Nec‐1), a potent inhibitor of necroptosis, to islet culture media could improve the recovery, maturation, and function of pre‐weaned porcine islets (PPIs). Methods: PPIs were isolated from pre‐weaned Yorkshire piglets (8‐15 days old) and either cultured in control islet culture media (n = 6) or supplemented with Nec‐1 (100 µM, n = 5). On days 3 and 7 of culture, islets were assessed for recovery, insulin content, viability, cellular composition, GLUT2 expression in beta cells, differentiation of pancreatic endocrine progenitor cells, function, and oxygen consumption rate. Results: Nec‐1 supplementation induced a 2‐fold increase in the insulin content of PPIs on day 7 of culture. When compared to untreated islets, Nec‐1 treatment doubled the beta‐ and alpha‐cell composition and accelerated the development of delta cells. Additionally, beta cells of Nec‐1‐treated islets had a significant upregulation in GLUT2 expression. The enhanced development of major endocrine cells and GLUT2 expression after Nec‐1 treatment subsequently led to a significant increase in the amount of insulin secreted in response to in vitro glucose challenge. Islet recovery, viability, and oxygen consumption rate were unaffected by Nec‐1. Conclusion: This study underlines the importance of necroptosis in islet cell death after isolation and demonstrates the novel effects of Nec‐1 to increase islet insulin content, enhance pancreatic endocrine cell development, facilitate GLUT2 upregulation in beta cells, and augment insulin secretion. Nec‐1 supplementation to culture media significantly improves islet quality prior to xenotransplantation.